2012
DOI: 10.1111/1462-2920.12060
|View full text |Cite
|
Sign up to set email alerts
|

Partaking of Archaea to biogeochemical cycling in oxygen‐deficient zones of meromictic saline Lake Faro (Messina, Italy)

Abstract: We used a combination of molecular and microbiological approaches to determine the activity, abundance and diversity of archaeal populations inhabiting meromictic saline Lake Faro (Messina, Italy). Analysis of archaeal 16S rRNA, amoA, accA and hbd genes and transcripts revealed that sub- and anoxic layers of Lake Faro are primarily inhabited by the organisms related to the clusters of Marine Group I.1a of Thaumarchaeota frequently recovered from oxygen-depleted marine ecosystems. These organisms dominated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 96 publications
2
27
0
Order By: Relevance
“…Ammonium reached the highest concentrations in the deep anoxic layers of the lakes, indicating a higher rate of mineralization than assimilation, coupled with a higher stability in the acidic pH range. The depth profiles of ammonium concentration were comparable for both Ursu and Fara Fund lakes, and similar to the ones described in other stratified lakes (Auguet et al, 2012;La Cono et al, 2013;Yau et al, 2013). The vertical profiles of nutrients (sulfate, sulfide, nitrite, nitrate and phosphate) were found to be a result of sedimentation, biogeochemical cycling or conservative mixing (Pasche et al, 2009), and were also comparable with those found in other studied lakes (Lepère et al, 2010;La Cono et al, 2013;Marteinsson et al, 2013).…”
Section: Water Chemistrysupporting
confidence: 86%
See 1 more Smart Citation
“…Ammonium reached the highest concentrations in the deep anoxic layers of the lakes, indicating a higher rate of mineralization than assimilation, coupled with a higher stability in the acidic pH range. The depth profiles of ammonium concentration were comparable for both Ursu and Fara Fund lakes, and similar to the ones described in other stratified lakes (Auguet et al, 2012;La Cono et al, 2013;Yau et al, 2013). The vertical profiles of nutrients (sulfate, sulfide, nitrite, nitrate and phosphate) were found to be a result of sedimentation, biogeochemical cycling or conservative mixing (Pasche et al, 2009), and were also comparable with those found in other studied lakes (Lepère et al, 2010;La Cono et al, 2013;Marteinsson et al, 2013).…”
Section: Water Chemistrysupporting
confidence: 86%
“…As a consequence, they commonly comprise an upper stratum where mixing occurs (mixolimnion), a stagnant lower one (monimolimnion) and an interposing boundary layer (chemocline) (Boehrer and Schultze, 2009). These lakes are important model systems for aquatic biology research, because their constant vertical stratification, steep chemical gradients and the presence of oxygen-deprived zones favor niche partitioning among prokaryotic populations, enabling the study of vertical zonations in microbially-mediated biogeochemical cycling (Lauro et al, 2011;Lopes et al, 2011;La Cono et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…3.1 (Copyright 1992–1995; Jandel Corporation). Differences were considered significant at P < 0.05, as described elsewhere (La Cono et al ., ).…”
Section: Methodsmentioning
confidence: 97%
“…The PCR products were further purified and sequenced at Macrogen (Amsterdam, Netherlands). Phylogenetic affiliation was performed as reported elsewhere (La Cono et al ., ).…”
Section: Methodsmentioning
confidence: 97%
“…For archaeal 16S rRNA gene amplification two different protocols were tested: a) primers 340f (5′-CCCTAYGGGGYGCASCAG-3′) and 1000r (5′-GAGARGWRGTGCATGGCC-3′) [32] with GoTaq Green Master Mix (Promega); b) primers Arc20f (5′-GTTTCCGGTTGATCCYGCCRG-3′) and Arc958r (5′-GTTTYCCGGCGTTGAMTCCAATT-3′) [33] with Takara's Ex Taq DNA Polymerase. No amplification of archaeal 16S rRNA genes was detected.…”
Section: Methodsmentioning
confidence: 99%